2014
DOI: 10.1055/s-0033-1363218
|View full text |Cite
|
Sign up to set email alerts
|

Erkrankungen der Halslymphknoten im Kindesalter

Abstract: The lymph nodes are an essential part of the body's immune system and as such are affected in many infectious, autoimmune, metabolic and malignant diseases. The cervical lymph nodes are particularly important because they are the first drainage stations for key points of contact with the outside world (mouth/throat/nose/eyes/ears/respiratory system) - a critical aspect especially among children - and can represent an early clinical sign in their exposed position on a child's slim neck. Involvement of the lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that age and sex are important factors for classifying neck masses 1 17 . In general, neck masses in children and young adults are more inflammatory than congenital and neoplastic diseases and are only found occasionally 4 . However, masses in older adults are often neoplastic 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that age and sex are important factors for classifying neck masses 1 17 . In general, neck masses in children and young adults are more inflammatory than congenital and neoplastic diseases and are only found occasionally 4 . However, masses in older adults are often neoplastic 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastatic carcinoma and lymphoma are the most common cervical malignant lesions, with cervical lymph node metastatic carcinoma accounting for approximately 3/4 of all malignant neck tumours. Most cervical malignant lesions (85%) include primary lesions located in the head and neck, and the most common lesions are nodal metastases of thyroid carcinoma (TC), salivary gland carcinoma (SC) and squamous cell carcinoma (SCC) 3 4 . Therefore, it would be valuable to identify the nature and types of cervical lymph node lesions before selecting clinical treatments 5 6 .…”
mentioning
confidence: 99%